Normal values ​​of potassium and sodium in children and their variations in dystrophic states - Botto Rada, Orestes (1954)
We have determined the serum potassium and hyponatremia 25 eutrophic children 1 12 months, 25 dystrophic 3 to 12 months and 30 pluricarenciales of 1-4 years. The mean value of serum potassium in eutrophic children from 0-1 year is 5.05 mEq/L. For the first half is 5.19 mEq/L., For the second semester 4.80 mEq/L. The rate of serum potassium gradually decreases as the child grows older. Extrapolating the regression line can be noticed that at 18 months or so, the child stabilizes its values ​​to the same level as the adult, while maintaining a higher coefficient of variation. Some negative correlation between the mean serum potassium and age was found in eutrophic. The mean value of serum sodium in eutrophic children from 0-1 year is 136.19 mEq/L. In the first half is 137.20 mEq/L. and second and 135.17 mEq/L. This ion is fixed under normal conditions, having a low coefficient of variation. In dystrophic children under one year of age, the mean value of serum potassium 4.90 mEq/L. In the first semester is 4.83 mEq/L. and the second is of 4.96 mEq/L. The serum sodium dystrophic the first year is 134.75 mEq/L. In the first half is 133.95 mEq/L. and the second 135.55 mEq/L. There is significant variation in the average values ​​of the electrolytes potassium and sodium in the dystrophic children. The average value of serum potassium in children pluricarenciales is 3.71 mEq/L., There consequently hypokalemia in those states. The average number of serum sodium in patients with pluricarenciales paintings reaches a value of 135.12 mEq/L. In the light of kwashiorkor serum sodium was not affected.